Coptic studies from Egypt to Los Angeles: essays in honor of Hany N. Takla - Agaiby, Elizabeth; Larsen, Lillian; Mikhail, Arsenius; Siuda, Tamara L.; Takla, Hany N. (Texts and studies in Eastern Christianity, 2026)
"Coptic Studies from Egypt to Los Angeles is a Festschrift in honor of Hany N. Takla and presents a collection of essays-many of which contain unpublished archival material-showcasing historical and liturgical aspects pertaining to Coptic Christianity. The volume brings together the work of senior and emerging scholars and covers six themes that mirror the broad range of multifaceted fields characterizing Takla's scholarly interests. Simultaneously, the themes also register close alignment with primary centers of ongoing research, including Coptic-Arabic Manuscripts, Coptic Art and History, Coptic Bible, Coptic Culture, Coptic Liturgy and Shenoute and Monasticism"-- Provided by publisher